A nonverbal communication interpretation of the deaf - Nogueira, Rosiléa Alves; Caetano, Joselany Áfio; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2000)
The deaf person develops a non-oral self-communication system. They can use Brazilian signal or commune cote by means of gesture language and body expressions to get through special meanings in their communication. Health professionals, in general, do not know very well this kind of communication as a result the interaction with these people because more difficult. The authors of this study try to interpretive the nonverbal elements used in the interaction of a deaf group of the Deaf Association of Ceará, in Fortaleza. For of this communication they filmed a group for 30 minutes while they were communicating. Then, the content was analyzed under Bardin’s optic. The nonverbal elements were distinguished in two subjects: sing and behavior. The study showed that positive and negative communications are made in universal way; there is exacerbation of face expression, there are gestures accompanied by lip movements and there are impossibilities to keep secret on the discussed subjects. While we were observing the behavior, a participation of all the elements of the group, but the communication is dissolved in sub-groups in some moments of the interaction. The vision plays a role of establishment of the emitter-receiver of the message in the interaction and the touch of the emphasis in the flame of the other’s attention. The results show the great potential of the nonverbal communication and the necessity of the use means of communication, beyond the speech during the interaction in this group.